2022
DOI: 10.1371/journal.pone.0270855
|View full text |Cite
|
Sign up to set email alerts
|

Factors associated with HIV viral suppression among adolescents in Kabale district, South Western Uganda

Abstract: Background The goal of antiretroviral therapy is to achieve sustained human immune deficiency virus (HIV) viral suppression. However, research on factors associated with viral load suppression among adolescents in low and middle-income countries is limited. The objectives of this study were to determine HIV viral suppression levels among adolescents in Kabale district and the associated clinical, adherence and psychosocial factors. Methods Cross-sectional and retrospective cohort study designs were used. Two… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 37 publications
2
5
0
Order By: Relevance
“…In this study, poor level of adherence and fair level of adherence showed a high proportion of non-viral suppression (14.8%; X 2 =18.55; P= <0.001), a significantly high proportion of non-viral suppression among poor adherence also reported from Amhara region, Ethiopia [25] and Kenya [30]. Exposure to opportunistic infection was one of the associated factors for HIV viral non-suppression in this study, which is in line with the results reported from Uganda [33] and Ethiopia [34], even though both studies were performed on all Adult HIV patients who were taking ART.…”
Section: Discussionsupporting
confidence: 90%
“…In this study, poor level of adherence and fair level of adherence showed a high proportion of non-viral suppression (14.8%; X 2 =18.55; P= <0.001), a significantly high proportion of non-viral suppression among poor adherence also reported from Amhara region, Ethiopia [25] and Kenya [30]. Exposure to opportunistic infection was one of the associated factors for HIV viral non-suppression in this study, which is in line with the results reported from Uganda [33] and Ethiopia [34], even though both studies were performed on all Adult HIV patients who were taking ART.…”
Section: Discussionsupporting
confidence: 90%
“…Treatment duration has been found to have a mixed effect on viral suppression. Studies conducted in Uganda and Kenya found no association between the two (25,26). Even though studies conducted in Ghana and Zimbabwe found that longer duration was associated with higher levels of viral suppression, the cutoff duration points were 3 years and 4.5 months, respectively (27,28).…”
Section: Discussionmentioning
confidence: 99%
“…3 For example, one study in south-central Uganda reported a viral suppression rate of 72.4% at the end of 2022; 4 another study conducted in south-western Uganda among adolescents found 81% viral suppression. 5 This threatens to stall progress in the HIV response towards the UNAIDS 95-95-95 HIV treatment targets by 2030. 6 Multiple studies, including a systematic review of studies in sub-Saharan Africa, have highlighted absence of transport as a potential barrier to antiretroviral therapy adherence.…”
Section: Introductionmentioning
confidence: 99%
“…3 For example, one study in south-central Uganda reported a viral suppression rate of 72.4% at the end of 2022; 4 another study conducted in south-western Uganda among adolescents found 81% viral suppression. 5 This threatens to stall progress in the HIV response towards the UNAIDS 95-95-95 HIV treatment targets by 2030. 6…”
Section: Introductionmentioning
confidence: 99%